A MEASUREMENT MODEL OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR PRACTICES AMONG SECONDARY TEACHERS : VALIDITY AND RELIABILITY - Ainon Madiah Mohd Nawawi (International Journal of Evaluation and Research in Education (IJERE), 2022)
The main issue for this study is about the practice of organizational citizenship behavior among teachers in secondary schools.  The purpose of this paper is to examine the reliability and validity of organizational citizenship behavior practice among secondary school teachers and develop a measurement model of teachers organizational citizenship behaviour. This study uses a cross -sectional survey study design using quantitative methods.  The total population for this study was 12 890 and the selected sample was 422 respondents. Organizational citizenship behavior  was measured using an educational organization citizenship behavior questionnaire instrument  by Eran Vigoda -Gadot et. all. Data and details collected were analyzed using Statistical Package for the Social Sciences (SPSS) Version 23 and Structural Equation Modeling (SEM AMOS)  Version 23. This study revealed that Cronbach’s Alpha values for all constructs were high. All items representing all three constructs were accepted and a model for organizational citizenship behavior could be developed.